2021
DOI: 10.3390/plants10010164
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Composition, Antioxidant Capacity and Antibacterial Activity of White Wormwood (Artemisia herba-alba)

Abstract: Artemisia herba-alba Asso. (Wormwood) is a wild aromatic herb that is popular for its healing and medicinal effects and has been used in conventional as well as modern medicine. This research aimed at the extraction, identification, and quantification of phenolic compounds in the aerial parts of wormwood using Soxhlet extraction, as well as characterizing their antimicrobial and anitoxidant effects. The phenolic compounds were identified in different extracts by column chromatography, thin layer chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 46 publications
1
46
0
Order By: Relevance
“…However, the problems associated with these antimicrobial drugs are their toxic effects and the resistance shown by microbes against these specific groups of antimicrobial agents. Therefore, these synthetic drugs have been replaced by naturally available plant products [ 22 , 40 ]. The current study was designed on the isolated compound (morin) by keeping in view the reported antibacterial action of E. umbellata plant extract [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the problems associated with these antimicrobial drugs are their toxic effects and the resistance shown by microbes against these specific groups of antimicrobial agents. Therefore, these synthetic drugs have been replaced by naturally available plant products [ 22 , 40 ]. The current study was designed on the isolated compound (morin) by keeping in view the reported antibacterial action of E. umbellata plant extract [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can be traced back to 1803 from the report on the isolation of morphine from Papaver somniferum ( Schmitz, 1985 ). Due to their effective applications as food supplements, herbal medicines, cosmetics as well as antibacterial activities, the phytochemicals have gained interest in the scientific community; and numerous phytochemicals have been validated for their antimicrobial potentials including against MDR strains ( Shriram et al, 2018 ; Anand et al, 2019 ; Yu et al, 2020 ; Mohammed et al, 2021 ). However, despite the reports on many phytochemicals, few have been approved by the Food and Drug Administration (FDA) such as codeine, capsaicin, reserpine, paclitaxel, colchicine, to name a few ( Kongkham et al, 2020 ).…”
Section: Phytochemicals For Combating Antibiotic Resistancementioning
confidence: 99%
“…Out of the alternative and effective options against MDR pathogens, plants might hold the key in providing the enormous range of the chemotherapeutics in form of their secondary metabolites with an ability to tackle bacterial infections ( Anand et al, 2019 ; Anand et al, 2020 ). These secondary metabolites or phytochemicals include the members of alkaloids, flavonoids, quinones, coumerins and many more ( Mbaveng et al, 2015 ; Anand et al, 2019 ; Anand et al, 2020 ; Mohammed et al, 2021 ). The current review depicts the potential role of the plant secondary metabolites or phyto-antimicrobials against the antibiotic resistant pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Rosemary oil has traditionally and largely been used as a medicinal herb with number of properties such as antiinflammatory, analgesic, astringent, antimicrobial, anti-rheumatic, carminative, antifungal, and antioxidant properties [8]. Natural phenolic compounds that have been found in plants and vegetables may decrease the risk of some diseases because of their antioxidant and free-radical inhibition potentials imparted by the benzene ring and the hydroxyl group in their structures [9][10][11]. These phenolic compounds are the result of secondary metabolism in plants, and are often utilized with the intention of therapeutic activity due to their pharmacological features [8,9].…”
Section: Introductionmentioning
confidence: 99%